PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI PENERIMAAN DAN PENGELUARAN KAS PADA PAUDQU NURUL HUDA - Upayarto, Budi; Septiani, Intan Tarisa (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2024)
The study aims to find out the procedures for cash receipts and disbursement information systems that are running to design cash receipts and disbursement information systems also to implement and test cash receipts and disbursements systems at PAUDQu Nurul Huda. PAUDQu Nurul Huda is a formal and non-formal educational institution ranging from 2-6 years old. Every operational activity that occurs at PAUDQu Nurul Huda requires funds that result in many transactions being carried out. The system currently used is manual recording which is still simple, resulting in inaccuracies in the results of calculations and recording. The method used to design and implement the system at PAUDQu Nurul Huda is a descriptive method, using the PIECES system analysis method and the waterfall system development method. Besides, to help make the application, the author uses the literature study method obtained from books and the internet related to this study. The final stage is system testing using the black-box testing method. The results of this study are in the form of an information system application for cash receipts and disbursements. The results of black-box testing show that the application is following the design that has been made and fulfills the functions needed in the form of processing, recording, and calculating data that is accurate and can be useful for the benefit of PAUDQu Nurul Huda.